Analisis Pengelolaan Sediaan Farmasi di Instalasi Farmasi Rumah Sakit di Kota Medan Tahun 2023 - Fendi Sipayung; Asriwati Asriwati; Ismail Efendy (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The management of pharmaceutical supplies in the Pharmacy Installation of a hospital consists of nine aspects: selection, demand planning, procurement, acceptance, storage, distribution, destruction and withdrawal, control, and administration. This study aims to analyze the management of pharmaceutical supplies at a hospital in Medan in 2023 using a qualitative method through direct observation and in-depth interviews with both primary and secondary data. Interviews were conducted with nine informants, including key informants, main informants, and supporting informants. The results of the study indicate that, overall, the management of pharmaceutical supplies is functioning well but not yet optimal. Three aspects that have been well implemented are selection, destruction and withdrawal, and administration. Meanwhile, siSwasta di Kota Medan other aspects, such as planning, procurement, acceptance, storage, distribution, and control, have not been fully optimized. The issue of medication shortages can be addressed through collaboration with eSwasta di Kota Medanternal pharmacies. To improve management, it is recommended that the hospital enhance the storage facilities, which are currently inadequate, by providing appropriate pallets and involving all related parties to work together in improving the system, as well as conducting regular monitoring and evaluation.